Insect Management for Legumes (Beans, Peas) - Susan E. Webb (EDIS, 2002)
This document is ENY-465 (which replaces ENY-420), one of a series of the Entomology & Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: July 2002. Revised: July 2003.